THE ROLE OF MODERN MEDIA IN STRENGTHENING SCOOP AMONG IRAQI JOURNALISTS: A FIELD STUDY ON IRAQI JOURNALISTS - Khamael Zidan Khalaf (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The Internet and the modern media have helped to bring about changes in the media environment and emerged new concepts such as the new media as a counterpart to traditional media and citizen journalism versus citizen journalism versus professional journalist, and the belief of media institutions about the importance of these new means and new concepts and the inadequacy of traditional sources in obtaining the news lead, the employees of the press institutions began to rely on the new media, including social networks to get the news ahead in order to serve their interests and enrich their press products and enhance their standing among the public. Hence this research came to take care of this problem, through which we will try to know the role of the new media in strengthening the journalistic lead of journalists working in Iraqi newspapers by demonstrating the importance of these means as a source of news and support for traditional sources. The research seeks to achieve a number of objectives: First, finding out why Iraqi journalists working for Iraqi newspapers use the new media. Second, how reliable are Iraqi journalists on the new media to achieve the journalistic foresight of information and its adoption as a source of news. Third, learn about the most important additions provided by the new media as a competitor to traditional sources in obtaining news in the work of journalism knowledge of the level of confidence in the new media and its adoption in the press ahead of.